PELAKSANAAN PEMBELAJARAN EKONOMI KELAS XI PASCA PANDEMI DI SMA NEGERI 4 BAUBAU - Sardiana, Sardiana; Adri, Jamal; Daslim, Daslim (JEC (Jurnal Edukasi Cendekia), 2024)
This study aims to understand how the teaching of economics for grade XI is conducted post-pandemic at SMA Negeri 4 Baubau. The method used is qualitative descriptive. The subjects of the study include 1 teacher, 1 vice principal of curriculum, and 10 grade XI students. The researcher serves as the main instrument, with data collection techniques involving observation, interviews, and documentation. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing. The results of the study indicate that the implementation of post-pandemic economics teaching at SMA Negeri 4 Baubau is effective. Face-to-face learning has returned to normal with adjustments to the K-13 curriculum. Communication between teachers and students is very good, with no significant barriers, and students are happy to interact directly. The response of students to face-to-face learning is very positive, seen from their enthusiasm for learning and meeting friends and teachers after two years of boring online learning. Student activities in the classroom are active; they frequently answer questions and ask about unclear material. Student learning outcomes after returning to face-to-face learning show significant improvement compared to during the pandemic, proving the effectiveness of this method